A study on the performance analysis of bioethanol produced from sugarcane molasses in SI engine - M.I.N, Ma'arof*; G.T., Chala; D,, Gunness; I, Saad (IOP Publishing, 2020)
Recently with ethanol being a renewable, bio-based and ecofriendly, it is projected to be the best replacement for petrol as a fuel in SI engines. Ethanol is derived mainly from sugarcane, cassava, corn and other waste biomass materials. These materials are rich in calories and could be utilized either as complements or as alternatives for conventional fuel sources. This paper aims to experimentally determine the properties of ethanol/gasoline blends and tests its performances in an SI engine. The E10, E20 and E30 ethanol-gasoline blends were studied and compared to gasoline fuel. It was found that the performance of the engine using bioethanol blends was almost comparable to that of pure gasoline, especially at lower ethanol content blends. Yet, increasing the ethanol content only gives adverse effects to the overall engine performance, resulting in 8.86% power loss at 2000 rpm for E20 and 8.18% for E30 compared to E0. Suggestively, with more research and experiments, bioethanol-fuel blends can replace pure gasoline fuels easily and with many added benefits on the same or slightly modified engines.